Haemophilus parasuis (Glaesserella parasuis) as a Potential Driver of Molecular Mimicry and Inflammation in Rheumatoid Arthritis - Di Sante, Gabriele; Gremese, Elisa; Tolusso, Barbara; Cattani, Paola; Di Mario, Clara; Marchetti, Simona; Alivernini, Stefano; Tredicine, Maria; Petricca, Luca; Palucci, Ivana; Camponeschi, Chiara; Aragon, Virginia; et al. (Frontiers in Medicine, 2021)
Background. Haemophilus parasuis (Hps, now Glaesserella parasuis) is an infectious agent which causes severe arthritis in swines and shares sequence similarity with residues 261-273 of Collagen type 2 (Coll261-273), a possible autoantigen in rheumatoid arthritis (RA). Objectives/methods: We tested the presence of Hps sequencing 16S ribosomal RNA in crevicular fluid, in synovial fluids and tissues in 100 patients with arthritis (RA and other peripheral arthritides) and in healthy controls. Moreover, we examined the cross-recognition of Hps by Coll261-273-specific T cells in HLA-DRB1*04pos RA patients, by T cell receptor (TCR) beta chain spectratyping and T cell phenotyping. Results. Hps DNA was present in 57.4% of the teeth crevicular fluids of RA patients and in 31.6% of controls. Anti-Hps IgM and IgG titers were detectable and correlated with disease duration and the age of the patients. PBMC were stimulated with Hps virulence-associated trimeric autotransporter peptide (VtaA10755-766), homologous to human Coll261-273 or co-cultured with live Hps. In both conditions the expanded TCR repertoire overlapped with Coll261-273 and led to the production of IL17. Discussion. We show that the DNA of an infectious agent (Hps), not previously described as pathogen in humans, is present in most patients with RA, and that an Hps peptide is able to activate T cells specific for Coll261-273, likely inducing or maintaining a molecular mimicry mechanism. Conclusion. The cross-reactivity between VtaA10755-766 of a non-human infectious agent and human Coll261-273 suggested an involvement in the pathogenesis of Rheumatoid Arthritis. This mechanism appears emphasized in predisposed individuals, such as patients sharing shared epitope.